Evaluation of Silicic Acid Sources for Spring Diatom Blooms on the Continental Shelf: Insights FromStable Silicon Isotopes in the East China Sea. Issue 2 (22nd February 2020) - Zhang, Anyu; Zhang, Jing; Liu, Sumei; Xuan, Jiliang; Zhu, Zhuoyi
Abstract: The concentration of dissolved silicic acid (DSi) and its isotopic composition (δ 30 Si(OH)4 ) were determined for the East China Sea (ECS) shelf in the spring season with high spatial resolution. DSi concentrations and δ 30 Si(OH)4 values ranged from 1.3 to 116.5 μM and +0.85‰ to +2.53‰, respectively. An enrichment of 30 Si was observed in most surface‐water samples compared with bottom waters. Several shallow‐water stations at water depths of <20 m reflected the overall control of biological utilization of DSi and regeneration of DSi from biogenic silica (BSi) on the distribution of δ 30 Si(OH)4 values. A seasonal difference in δ 30 Si(OH)4 values was observed in the euphotic zone of shelf waters, which is attributed mainly to continuous consumption of DSi in enhanced diatom blooms. The major water masses influencing the ECS shelf were characterized with distinct DSi concentrations and isotopic compositions. Using Si isotopic constraints, modeling of δ 30 Si(OH)4 values implied that utilization of DSi in the ECS occurred as if in a steady‐state mode. Riverine input was the major DSi source for the surface waters of inner‐shelf areas, as well as part of the middle‐ and outer‐shelf surface waters near the Changjiang River estuary. Upwelled Kuroshio Subsurface Water from the shelf break supported diatom growth in middle‐shelf surface waters. Taiwan Strait Warm Water and Kuroshio Surface Water were relatively oligotrophic, and their influence was confined to waters near the Taiwan Strait and the outer shelf and slope areas. Plain Language Summary: The continental shelf is characterized with spring diatom blooms, which are fed by a complex sources of dissolved silicic acid (DSi). The East China Sea (ECS) is a productive marginal sea, with active mixing among the freshwater and pelagic seawaters. The significant changes in the riverine nutrients (reduced DSi and elevated nitrogen and phosphorus loadings) due to human disturbance may impact the growth of diatoms in the ECS. In this scenario, we investigated the DSi concentration and silicon isotopic composition (δ 30 Si(OH)4 ) in the ECS with wide coverage and high spatial resolution. Based on the recognition of hydrological properties, DSi concentration and δ 30 Si(OH)4 of the major end‐members, we reproduced the distribution of δ 30 Si(OH)4 in the shelf surface waters by applying a steady‐state fractionation model under different mixing scenarios. The modeling calculation suggests that DSi‐rich riverine input is important to support the diatom growth in the inner shelf, while in the middle shelf, the DSi for the diatom's growth is mainly from the upwelled Kuroshio Subsurface Water. Our study in the ECS demonstrates the usefulness of δ 30 Si(OH)4 in discriminating the DSi source in a dynamic marginal sea environment and may have implications in the study of silicon cycle in river‐influenced coastal areas. Key Points: High‐spatial‐resolution study of DSi concentration and δ 30 Si(OH)4 are carried out in the East China Sea in spring Major end‐members influencing the East China Sea are characterized with distinct DSi concentration and silicon isotopic features Riverine‐DSi support diatoms growth in the inner shelf and upwelled Kuroshio Subsurface Water support the diatoms growth in the middle shelf